(untitled) (Development Engineering Conferences Center Articles Database, 2025)
With the environmental problems caused by traditional petroleum-based plastics, green packaging coatings have become an important non-polluting choice. The advances of biopolymer-based packaging materials are reviewed by recent research results in the manuscript, and are categorized fundamentally into three groups: polysaccharides (starch and cellulose), polyesters (PLA, PHA) and proteins (gelatin, whey). More indication depicting that the mechanical and barrier qualities and performances of these coatings can be enhanced much by incorporation with nanomaterials or bioactive compounds has been shown recently. Such modifications have led to active and intelligent packaging systems, with improved antimicrobial, antioxidant, and UV light barrier properties that can extend shelf life and improve the safety of foods. Furthermore, upcycling of agricultural waste conforms to the tenets of a circular economy, which advocates for valorization of low-cost residues into high-value biodegradable packaging. There are plenty of other challenges, not least of which cost, scale and performance on a par with old ingredients, but formulation and processing advances are sitting corners and champions are emerging that can lead us to a greener (in both senses) future for packaging.